Preparation method of levextrel resin and application of levextrel resin in purification of ammonium rhenate
By preparing the extracted resin with excellent performance during the purification process of ammonium rhenate, the problem of poor effect of existing resins in purification of ammonium rhenate is solved, and an efficient purification and environmentally friendly process flow is achieved.
Patent Information
- Application Number
- CN202510186401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-20
AI Technical Summary
The existing extractive resins have poor results in the purification process of ammonium rhenate, and the extractant is unevenly dispersed, poor binding force and easy loss.
By setting the ratio of the oil-phase mixed liquid and the aqueous mixed liquid and performing precise temperature control, an extractive resin with excellent performance was prepared. The method includes reacting the resin particles with a specific ratio of oil-phase mixed liquid and aqueous-phase mixed liquid at a temperature of 55°C to 65°C to ensure uniform dispersion and firm bonding of the extractant.
The efficient purification of ammonium rhenate is achieved, and products with a purity of more than 99.99% are obtained, while reducing the generation of organic waste liquid, reducing the impact on the environment, and simplifying the synthesis and regeneration process of resins.
Smart Images

Figure CN119657101A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of metal purification, and in particular to a method for preparing a leaching resin and an application thereof in purifying ammonium rhenate. Background Art
[0002] Metal rhenium has high melting point, high strength, high density, good plasticity and excellent mechanical stability. Ammonium rhenate is the raw material for preparing high-purity metal rhenium, and the purity of ammonium rhenate determines the quality of rhenium metal. Therefore, mastering the refining technology of ammonium rhenate is of great significance to ensure the strategic resource demand for the development of my country's aerospace industry.
[0003] At present, the main methods for refining and purifying ammonium rhenate include extraction, ion exchange, recrystallization, membrane separation technology, biochar adsorption, etc. Among them, extraction and ion exchange are the most widely used methods, but both extraction and ion exchange have certain limitations. The research and application of leaching resins have developed rapidly in recent years. They are mainly used in water treatment, rare earth separation and other fields. The method is to prepare the extractant by adsorbing it on a macroporous polymer carrier.
[0004] However, the currently used leaching resins still have certain problems, such as poor purification effect of existing leaching resins on ammonium rhenate, uneven dispersion of the extractant, poor binding force with the resin, and easy loss. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for preparing a leaching resin and its application in purifying ammonium rhenate. By setting the ratio of the oil phase mixed liquid and the water phase mixed liquid, and accurate temperature control, a leaching resin with excellent performance is prepared. The leaching resin not only has a uniform dispersion of the extractant, but also has a strong binding force with the resin and is not easy to lose. When the leaching resin is used to purify the ammonium rhenate solution in a chromatographic column, by controlling the solution concentration and flow rate, ammonium rhenate with a purity greater than 99.99% can be obtained. The leaching resin prepared by the method provided by the present invention can not only improve the purification efficiency and purity of ammonium rhenate, but also reduce the generation of organic waste liquid, reduce the impact on the environment, and simplify the synthesis and regeneration process of the resin, improve the economy and environmental protection of ammonium rhenate refining technology, and provide high-quality rhenium metal resource guarantee for the development of my country's aerospace industry.
[0006] In a first aspect, the present invention provides a method for preparing a leaching resin, the method comprising: The resin particles are added to an equal volume of pure water at a temperature of 55°C to 65°C, the oil phase mixture is added to the obtained system, stirred, cooled, and then the water phase mixture is added, stirred, filtered, and washed to obtain the leaching resin; Wherein, the volume ratio of the resin particles to the oil phase mixed liquid is 1:(0.4-0.7); the volume ratio of the oil phase mixed liquid to the water phase mixed liquid is 1:(0.6-0.75); The oil phase mixed liquid is composed of 65% to 80% by weight of a diluent, 20% to 30% of a lipid compound and 5% to 10% of octanol; The aqueous phase mixed liquid is composed of 35% to 50% pure water, 25% to 45% ammonia water and 5% to 10% sodium hydroxide in percentage by mass.
[0007] Optionally, the volume ratio of the resin particles to the oil phase mixed liquid is 1:(0.5-0.6).
[0008] Optionally, the lipid compound is diisooctyl phosphate and / or 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester.
[0009] Optionally, the diluent is 260# sulfonated kerosene, n-dodecane or xylene.
[0010] Optionally, the method for preparing the resin particles comprises: Gul gum and gelatin are added to pure water at a temperature of 70°C to 80°C, hydrocarbon compounds, sodium dodecylbenzene sulfonate, an initiator, sodium carboxymethyl cellulose and calcium sulfate are added to the obtained colloidal solution, mixed at 90°C to 95°C, kept warm for 2h to 4h, cooled, filtered and washed to obtain the resin particles; Wherein, the hydrocarbon compound is at least one of styrene, methacrylic acid and divinylbenzene; The initiator is a peroxide initiator or an azo initiator.
[0011] Optionally, in the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 5% to 10%, 25% to 40%, 15% to 30%, 10% to 15%, 5% to 10%, 2% to 6%, and 1% to 5%, respectively.
[0012] Optionally, in the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 7% to 9%, 30% to 35%, 20% to 25%, 11% to 13%, 6% to 8%, 2% to 6% and 1% to 5%, respectively.
[0013] Optionally, the hydrocarbon compound is styrene, methacrylic acid and divinylbenzene; The mass percentages of the styrene, the methacrylic acid and the divinylbenzene are (45-55)%: (20-25)%: (20-25)%.
[0014] Optionally, the peroxide initiator is benzoyl peroxide, dicumyl peroxide or di-tert-butyl peroxide; The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0015] In a second aspect, the present invention provides an application of a leaching resin in purifying ammonium rhenate, wherein the leaching resin is prepared by the preparation method described in the first aspect, and the leaching resin is used for purifying ammonium rhenate; The purification method comprises: An ammonium rhenate solution with a concentration of no more than 35 g / L is injected into the chromatography column containing the leaching resin at a flow rate of 2 Bv~7 Bv, and ammonium rhenate with a purity greater than 99.99% is obtained after passing through.
[0016] Beneficial technical effects: 1. The present invention provides a method for preparing a leaching resin, wherein the method comprises reacting resin particles with a specific ratio of an oil phase mixed liquid and an aqueous phase mixed liquid at a temperature of 55°C to 65°C to prepare a high-performance leaching resin; the resin has the characteristics of uniform dispersion of the extractant, strong binding force with the resin, and high stability, and can effectively reduce the loss of the extractant, reduce the generation of organic waste liquid, and thus reduce the impact on the environment; the method simplifies the synthesis process of the resin, improves the recycling efficiency of the resin, and provides a reliable material basis for the efficient purification of ammonium rhenate; 2. The present invention provides an application of a leaching resin in purifying ammonium rhenate. When applied, an ammonium rhenate solution with a concentration of no more than 35 g / L is injected into a chromatography column containing the leaching resin, and the flow rate is controlled within the range of 2 Bv to 7 Bv, and ammonium rhenate with a purity greater than 99.99% can be finally obtained; the leaching resin prepared by the preparation method provided by the present invention can not only improve the purification efficiency and product purity of ammonium rhenate, but also avoid the limitations of traditional extraction methods and ion exchange methods, such as large organic phase loss, complex resin synthesis, and limited number of recycling and regeneration times; at the same time, the process is simple to operate, environmentally friendly, reduces the discharge of organic waste liquid, reduces production costs, and provides high-quality rhenium metal raw materials for aerospace and other fields, which has important strategic significance and economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the description of the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0018] Figure 1 A flow chart of a method for preparing a leaching resin proposed in an embodiment of the present application is shown. DETAILED DESCRIPTION
[0019] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0020] In the drawings, the size of the constituent elements, the thickness of the layer or the area may be exaggerated for the sake of clarity. Therefore, any implementation of the present disclosure is not necessarily limited to the size shown in the drawings, and the shapes and sizes of the components in the drawings do not reflect the true proportions. In addition, the drawings schematically show ideal examples, and any implementation of the present disclosure is not limited to the shapes or values shown in the drawings.
[0021] In the relevant technology, metallic rhenium has high melting point, high strength, high density, good plasticity and excellent mechanical stability. It has very good heat shock resistance at high temperature. At the same time, rhenium also has very good wear resistance, corrosion resistance and chemical inertness. It has good creep resistance under high temperature and rapid cooling and heating conditions. Due to its excellent properties, it is widely used in industries such as petrochemicals, aerospace and electronics, especially in some high-tech fields related to national security and national development strategies. It plays an irreplaceable role, such as the manufacture of single crystal turbine blades for aircraft engines. Rhenium is indispensable. However, trace impurities with low melting and boiling points in rhenium metal are prone to form inclusion cores and cause the decay of mechanical properties of single crystal high-temperature alloy materials, thereby affecting the safety performance of aircraft. Therefore, the requirements for trace impurity elements in rhenium metal are extremely strict. Ammonium rhenate is the raw material for preparing high-purity metallic rhenium, and the purity of ammonium rhenate determines the quality of rhenium metal. Therefore, mastering the refining technology of ammonium rhenate is of great significance to ensuring the strategic resource needs for the development of my country's aerospace industry.
[0022] At present, the main methods for refining and purifying ammonium rhenate include extraction, ion exchange, recrystallization, membrane separation technology, biochar adsorption, etc. Among them, extraction and ion exchange are the most widely used methods, but both have certain limitations, such as large organic phase loss in the extraction method and organic waste liquid will have a certain impact on the environment, and complex resin synthesis in the ion exchange method and limited number of cycles and regeneration.
[0023] The research and application of leaching resins have developed rapidly in recent years. They are mainly used in water treatment, rare earth separation and other fields. They are prepared by adsorbing the extractant onto a macroporous polymer carrier. They have the high selectivity and high efficiency of solvent extraction and the simplicity and pollution-free nature of ion exchange technology. They also overcome the difficulties in stratification of some extractants and the complex synthesis of ion exchange resins and chelating resins. However, leaching resins still have certain problems, such as the poor purification effect of existing leaching resins on ammonium rhenate, uneven dispersion of the extractant, poor binding force with the resin, and easy loss.
[0024] In view of the problems existing in the related art, the present invention provides a method for preparing a leaching resin. Figure 1 , the method comprising: Step S1: adding resin particles into an equal volume of pure water at a temperature of 55°C to 65°C, adding an oil phase mixed liquid into the obtained system, stirring, and cooling; Step S2: adding the aqueous phase mixture, stirring, filtering and washing to obtain the leaching resin; Wherein, the volume ratio of the resin particles to the oil phase mixed liquid is 1:(0.4-0.7); the volume ratio of the oil phase mixed liquid to the water phase mixed liquid is 1:(0.6-0.75); The oil phase mixed liquid is composed of 65% to 80% by weight of a diluent, 20% to 30% of a lipid compound and 5% to 10% of octanol; The aqueous phase mixed liquid is composed of 35% to 50% pure water, 25% to 45% ammonia water and 5% to 10% sodium hydroxide in percentage by mass.
[0025] It should be noted that the resin particles are styrene gel-type resins; The pore size of the resin particles is 0.5 nm to 5 nm; The oil phase mixed liquid and the water phase mixed liquid constitute the extractant, and the molecules in the oil phase mixed liquid and the water phase mixed liquid are loaded in the pores of the resin particles; The temperature of pure water can be 55 ℃, 56 ℃, 57 ℃, 58 ℃, 59 ℃, 60 ℃, 61 ℃, 62 ℃, 63 ℃, 64 ℃, 65 ℃; within this temperature range, the resin particles can fully swell, so that their pore size is enlarged, which is convenient for the extractant (oil phase mixture and water phase mixture) to enter the interior of the resin and disperse evenly; and, higher temperature helps to reduce the viscosity of the subsequent oil phase mixture, so that lipid compounds and 2-octanol are more easily dispersed on the surface and inside of the resin; and, the increase in temperature can accelerate the chemical reaction rate between ammonia water and sodium hydroxide and the resin surface or the extractant, and promote the firm bonding of the extractant and the resin; The volume ratio of the resin particles to the oil phase mixture can be 1:0.4, 1:0.5, 1:0.6, 1:0.7; The volume ratio of the oil phase mixture to the water phase mixture can be 1:0.6, 1:0.65, 1:0.7, 1:0.75; The mass percentage of the diluent can be 65%, 70%, 75%, 80%; the diluent can reduce the viscosity of the oil phase mixture, making it easier to disperse on the surface and inside of the resin. At the same time, the diluent can also adjust the polarity of the oil phase mixture, making it more suitable for combining with the resin particles; The mass percentage of the lipid compound can be 20%, 22%, 24%, 26%, 28%, and 30%; the lipid compound is the main component of the extractant, which can selectively form a complex with the rhenium ion in the ammonium rhenate, thereby realizing the separation and purification of rhenium; The mass percentage of 2-octanol can be 5%, 6%, 7%, 8%, 9%, and 10%. 2-octanol, as a cosolvent and surfactant, can enhance the dispersibility of the extractant (oil phase and water phase) on the resin surface, improve the binding force between the extractant and the resin, and reduce the loss of the extractant. The mass percentage of pure water can be 35%, 40%, 45%, 50%; pure water is used as a solvent to dissolve sodium hydroxide and provide a reaction medium; The mass percentage of ammonia water can be 25%, 30%, 35%, 40%, and 45%; the main function of ammonia water is to adjust the pH value of the aqueous phase mixture to make it alkaline. Under alkaline conditions, ammonium rhenate is more likely to react with rhenate ions (ReO 4- ) in the form of , which is convenient for selective adsorption by the extractant; The mass percentage of sodium hydroxide can be 5%, 6%, 7%, 8%, 9%, and 10%; sodium hydroxide can further strengthen the alkaline environment of the aqueous phase mixture, and can react with the functional groups on the surface of the resin to enhance the adsorption capacity of the resin for the extractant; The stirring in step S1 can make the resin particles fully contact with the oil phase mixture, ensuring that the extractant is evenly dispersed on the surface and inside of the resin; The cooling process in step S1 helps the resin particles to solidify, so that the extractant is firmly bound to the resin to prevent it from being lost in subsequent steps; The filtration in step S2 is to separate the unabsorbed oil phase mixed liquid and the water phase mixed liquid to obtain the leaching resin loaded with the extractant; The washing in step S2 is to remove the unreacted substances and impurities remaining on the surface of the resin and improve the purity of the leaching resin.
[0026] In the present invention, by controlling the ratio of resin particles to oil phase mixed liquid and the ratio of oil phase mixed liquid to water phase mixed liquid, the extractant can be evenly dispersed and firmly combined on the resin carrier to reduce the loss of the extractant during application. Among them, the combination of diluent, lipid compound and sec-octanol in the oil phase mixed liquid, and the ratio of pure water, ammonia water and sodium hydroxide in the water phase mixed liquid further enhance the adsorption capacity and selectivity of the leaching resin, and can improve the purity of ammonium rhenate during application.
[0027] The preparation method provided by the present invention is not only simple to operate, but also reduces the generation of organic waste liquid, reduces the impact on the environment, and has high industrial application value. The prepared leaching resin can be used to purify ammonium rhenate. By adjusting the ratio of resin particles, oil phase and water phase mixed liquid and process conditions, the adsorption capacity and selectivity of the leaching resin can be effectively improved, the loss of the extractant can be reduced, and the purification effect of ammonium rhenate can be improved.
[0028] In some embodiments, the volume ratio of the resin particles to the oil phase mixture is 1:(0.5-0.6).
[0029] It should be noted that the volume ratio of resin particles to oil phase mixture can be 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58, 1:0.6; by precisely controlling the amount of oil phase mixture, it helps to reduce the waste of organic solvents and the amount of organic waste liquid generated, thereby reducing production costs and reducing pollution to the environment, which is in line with the development concept of green chemistry.
[0030] In the present invention, by setting the volume ratio of the resin particles to the oil phase mixed liquid, while ensuring that the extractant is evenly dispersed on the surface and inside of the resin and improving the adsorption performance of the leaching resin, the extractant can be more closely combined with the resin, reducing the loss of the extractant during subsequent use, and improving the stability and service life of the leaching resin. The even dispersion and firm combination of the extractant on the resin can further improve the selective adsorption capacity of the leaching resin for ammonium rhenate.
[0031] In some embodiments, the lipid compound is diisooctyl phosphate and / or 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester.
[0032] It should be noted that the lipid compound may be diisooctyl phosphate or 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester; the lipid compound may be diisooctyl phosphate and 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester.
[0033] In the present invention, dioctyl phosphate and 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester are both highly efficient selective extractants for rhenate ions (ReO 4- ) has a strong complexing ability and can form a stable complex with the rhenium ions in ammonium rhenate, thereby improving the selective adsorption capacity of the leaching resin for ammonium rhenate. These two extractants not only have higher selectivity for rhenium, but also can effectively reduce the interference of other impurity ions (such as molybdenum, tungsten, etc.), thereby improving the purification efficiency of ammonium rhenate.
[0034] In specific implementation, diisooctyl phosphate and 2-ethylhexyl phosphonate have longer carbon chain structures and stronger polar groups (such as phosphate groups), which can form stronger chemical bonds or physical adsorption with the functional groups on the surface of the resin, thereby reducing the loss of the extractant during the purification process and improving the stability and service life of the leaching resin.
[0035] In specific implementation, diisooctyl phosphate and 2-ethylhexyl phosphonate have good solubility and low viscosity, and can form a uniform oil phase mixture with the diluent and 2-octanol, which helps to evenly disperse the extractant in the resin particles and avoid the problem of local overload or underload.
[0036] In specific implementation, the above two extractants have high chemical stability under alkaline conditions (provided by ammonia water and sodium hydroxide in the aqueous phase mixture), are not easy to decompose or fail, thereby ensuring the long-term performance of the leaching resin.
[0037] In some embodiments, the diluent is 260# sulfonated kerosene, n-dodecane or xylene.
[0038] In the present invention, 260# sulfonated kerosene, n-dodecane and xylene all have good solubility and low viscosity, can effectively dissolve lipid compounds and octanol, and form a uniform oil phase mixed liquid, thereby facilitating the uniform dispersion of the extractant in the resin particles, avoiding the problem of local overload or underload, improving the adsorption performance of the leaching resin, and further improving the adsorption capacity and selectivity, thereby improving the purification efficiency and purity of the leaching resin for ammonium rhenate.
[0039] In specific implementation, the above diluent has suitable polarity and surface tension, can form good interaction with the functional groups on the surface of the resin, and enhance the binding force between the extractant and the resin. In particular, 260# sulfonated kerosene, because it contains sulfonated groups, can form stronger physical or chemical adsorption with polar groups (such as carboxyl groups, etc.) on the surface of the resin, thereby reducing the loss of the extractant during the purification process.
[0040] In some embodiments, the method for preparing the resin particles comprises: adding guar gum and gelatin into pure water at a temperature of 70°C to 80°C, adding a hydrocarbon compound, sodium dodecylbenzene sulfonate, an initiator, sodium carboxymethyl cellulose and calcium sulfate to the obtained colloidal solution, mixing at 90°C to 95°C, keeping the temperature for 2 h to 4 h, cooling, filtering and washing to obtain the resin particles; Wherein, the hydrocarbon compound is at least one of styrene, methacrylic acid and divinylbenzene; The initiator is a peroxide initiator or an azo initiator.
[0041] It should be noted that the temperature of pure water can be 70 ℃, 72 ℃, 74 ℃, 76 ℃, 78 ℃, and 80 ℃; Gul gum and gelatin, as colloidal matrices, are mainly used to form the basic skeleton of resin particles. Both have good gelling properties and biocompatibility, and can improve the mechanical strength and chemical stability of resin particles. Gul gum and gelatin can synergize with sodium carboxymethyl cellulose and calcium sulfate to further enhance the structural stability of resin particles. Sodium dodecylbenzene sulfonate is a surfactant, mainly used to emulsify hydrocarbon compounds and make them evenly dispersed in colloidal solutions to form uniform resin particles; Sodium carboxymethyl cellulose and calcium sulfate are used as reinforcing agents to improve the mechanical strength and stability of resin particles. Sodium carboxymethyl cellulose can increase the flexibility of resin particles, while calcium sulfate can enhance the hardness and wear resistance of resin particles. After adding hydrocarbon compounds, sodium dodecylbenzene sulfonate, initiator, sodium carboxymethyl cellulose and calcium sulfate to the obtained colloidal solution, the mixture can be mixed at 90°C, 91°C, 92°C, 93°C, 94°C and 95°C and kept warm for 2 h, 2.5 h, 3 h, 3.5 h and 4 h.
[0042] In the present invention, by using guar gum and gelatin as colloidal matrices, and combining sodium carboxymethyl cellulose and calcium sulfate as reinforcing agents, the mechanical strength and stability of the prepared resin particles are significantly improved, so that they can withstand higher operating pressures, reduce breakage and wear during the purification process, and extend the service life of the final product leaching resin.
[0043] In a specific implementation, the addition of hydrocarbon compounds, combined with the action of the initiator, can form macroporous resin particles with uniform pore size distribution and high specific surface area. This structure is conducive to the uniform dispersion and firm binding of the extractant in the resin particles, thereby improving the adsorption performance of the leaching resin. In a specific implementation, guar gum and gelatin, as natural polymer materials, have good chemical stability and biocompatibility. Combined with the emulsification effect of sodium dodecylbenzene sulfonate, the resin particles exhibit excellent chemical stability under alkaline conditions (provided by ammonia water and sodium hydroxide in the aqueous phase mixture) when preparing the leaching resin, and are not easy to decompose or fail.
[0044] In some embodiments, in the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 5% to 10%, 25% to 40%, 15% to 30%, 10% to 15%, 5% to 10%, 2% to 6%, and 1% to 5%, respectively.
[0045] It should be noted that the mass percentage of gul gum can be 5%, 6%, 7%, 8%, 9%, 10%; The mass percentage of gelatin can be 25%, 27%, 29%, 30%, 32%, 35%, 37%, 40%; The mass percentage of hydrocarbon compounds may be 15%, 17%, 20%, 23%, 25%, 27%, 30%; The mass percentage of sodium dodecylbenzene sulfonate can be 10%, 11%, 12%, 13%, 14%, 15%; The mass percentage of the initiator can be 5%, 6%, 7%, 8%, 9%, 10%; The mass percentage of sodium carboxymethyl cellulose can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%; The mass percentage of calcium sulfate can be 1%, 2%, 3%, 4%, or 5%.
[0046] In the present invention, guar gum and gelatin are used as colloidal matrices to provide the basic skeleton of the resin particles. The high proportion of gelatin ensures the mechanical strength and toughness of the resin particles, and the addition of guar gum further enhances the stability and pressure resistance of the particles. Sodium carboxymethyl cellulose and calcium sulfate are used as reinforcing agents to further improve the hardness and wear resistance of the resin particles, so that they can withstand higher operating pressures and reduce breakage and wear during the purification process. The proportion of hydrocarbon compounds is adjusted to form a uniform macroporous structure in the polymerization reaction. This structure has a high specific surface area, which is conducive to the uniform dispersion and firm bonding of the extractant in the resin particles, thereby improving the adsorption performance of the leaching resin. Sodium dodecylbenzene sulfonate is used as a surfactant to ensure the uniform dispersion of hydrocarbon compounds in the colloidal solution, thereby forming resin particles with stable structure. The proportion of the initiator is set to effectively control the rate of the polymerization reaction, avoid the problem of uneven resin structure caused by too fast or too slow reaction, and thus improve the chemical stability of the resin particles.
[0047] In some embodiments, in the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 7% to 9%, 30% to 35%, 20% to 25%, 11% to 13%, 6% to 8%, 2% to 6%, and 1% to 5%, respectively.
[0048] In the present invention, by optimizing the mass percentage of each component, the dosage of each component can be reduced while achieving the best effect of each component, thereby avoiding waste of resources, saving costs, reducing waste liquid production, and reducing impact on the environment.
[0049] In some embodiments, the hydrocarbon compounds are styrene, methacrylic acid, and divinylbenzene; The mass percentages of the styrene, the methacrylic acid and the divinylbenzene are (45-55)%: (20-25)%: (20-25)%.
[0050] It should be noted that the mass percentages of styrene, methacrylic acid and divinylbenzene may be (45:20:20)%, (50:22:21)%, (50:20:25)%, (55:25:25)% and the like.
[0051] In the present invention, styrene is used as the main monomer to form resin particles with larger pore size and higher specific surface area. This structure is conducive to the uniform dispersion and firm binding of the extractant in the resin particles, thereby improving the adsorption performance of the leaching resin. Methacrylic acid and divinylbenzene further adjust the pore size distribution and crosslinking degree of the resin particles, so that the resin particles have more uniform pore size and higher mechanical strength.
[0052] In specific implementation, the copolymerization of styrene and divinylbenzene can form a cross-linked structure, thereby improving the mechanical strength and chemical stability of the resin particles. Such high-strength resin particles can withstand higher operating pressures, reduce breakage and wear during the purification process, and help extend the service life of the leaching resin.
[0053] In specific implementation, the addition of methacrylic acid introduces a carboxyl functional group, which can form a stronger chemical bond with other functional groups on the surface of the resin, further enhancing the chemical stability of the resin particles.
[0054] In some embodiments, the peroxide initiator is benzoyl peroxide, dicumyl peroxide or di-tert-butyl peroxide; The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0055] In the present invention, peroxide initiators and azo initiators have different decomposition temperatures and reaction activities, and suitable initiators can be selected according to process requirements, thereby accurately controlling the rate and degree of the polymerization reaction, avoiding the problem of uneven resin structure caused by too fast or too slow polymerization reaction, thereby forming resin particles with uniform pore size distribution and high specific surface area.
[0056] In a specific implementation, the peroxide initiator and the azo initiator can effectively initiate the polymerization reaction of styrene, methacrylic acid and divinylbenzene to form a cross-linked structure and obtain high-strength resin particles.
[0057] The present invention also provides an application of a leaching resin in purifying ammonium rhenate, wherein the leaching resin is prepared by the above-mentioned preparation method, and the leaching resin is used for purifying ammonium rhenate; The purification method comprises: An ammonium rhenate solution with a concentration of no more than 35 g / L is injected into the chromatography column containing the leaching resin at a flow rate of 2 Bv~7 Bv, and ammonium rhenate with a purity greater than 99.99% is obtained after passing through.
[0058] It should be noted that the selection of an ammonium rhenate solution with a concentration of no more than 35 g / L can ensure the adsorption efficiency and selectivity of the leaching resin to ammonium rhenate; The flow rate can be set to 2 Bv, 3 Bv, 4 Bv, 5 Bv, 6 Bv, and 7 Bv. The flow rate is one of the key factors affecting the purification effect of the chromatography column. A flow rate that is too fast (>7 Bv) may result in insufficient contact time between the ammonium rhenate solution and the leaching resin, reducing the adsorption efficiency. A flow rate that is too slow (<2 Bv) will result in low production efficiency. The flow rate range of 2 Bv~7 Bv can improve production efficiency while ensuring adsorption efficiency. After use, the leaching resin can be regenerated by an eluent (such as a dilute acid or alkaline solution) to remove the adsorbed impurity ions and restore its adsorption capacity. The regenerated leaching resin can be recycled many times, thereby reducing production costs and environmental impact.
[0059] In the present invention, the Figure 1 The leaching resin prepared by the preparation method shown is used to purify ammonium rhenate, which can significantly improve the purification efficiency and purity of ammonium rhenate compared with traditional leaching resins. The high selectivity and strong adsorption capacity of the leaching resin for ammonium rhenate ensure that the impurity ions (such as molybdenum, tungsten, etc.) in the ammonium rhenate solution are effectively removed, thereby obtaining an ammonium rhenate product with a purity greater than 99.99%.
[0060] In specific implementation, the chromatography column operation method proposed in the present invention is simple and easy to operate, and has high operability and repeatability. By controlling the flow rate within the range of 2 Bv to 7 Bv, the problem of insufficient adsorption caused by too fast a flow rate or low production efficiency caused by too slow a flow rate can be avoided.
[0061] In summary, the purification method of the present invention can obtain an ammonium rhenate product with a purity greater than 99.99%, which meets the strict requirements of the aerospace and other fields for high-performance rhenium materials. This high-purity ammonium rhenate is a key raw material for preparing high-purity metallic rhenium, and is of great significance to ensuring the strategic resource needs of my country's aerospace industry.
[0062] In order to enable those skilled in the art to more clearly understand the present invention, the preparation method of a leaching resin according to the present invention and its application in purifying ammonium rhenate are now described in detail through the following examples.
[0063] Example 1 A leaching resin is prepared, comprising: (1) Mix 50 ml of ultrapure water, 40 ml of aqueous ammonia and 10 g of sodium hydroxide to obtain an aqueous phase mixture; (2) Mix 75 ml of 260# sulfonated kerosene, 20 ml of diisooctyl phosphate and 5 ml of sec-octanol to obtain an oil phase mixture; (3) Add 5 g of guar gum and 35 g of gelatin into pure water at a temperature of 80 °C, stir and dissolve, then add 15 g of styrene, 8 g of divinylbenzene, 7 g of methacrylic acid, 13 g of sodium dodecylbenzene sulfonate, 4 g of sodium carboxymethyl cellulose, 3 g of calcium sulfate and 10 g of azobisisobutyronitrile to the obtained colloidal solution in sequence, heat to 95 °C, then stir and mix thoroughly, keep warm for 2 h, then cool, filter and wash to obtain the desired solid phase resin particles; (4) The obtained solid phase resin particles are added to an equal volume of pure water, and the temperature of the pure water is controlled to be 60 °C. The above oil phase mixture is slowly added to the obtained system with slight stirring during the addition process. The volume ratio of the solid phase particles to the oil phase mixture added thereto is 1:0.6. Stir for 30 min, keep warm for 1 h, and then cool to room temperature. The above prepared water phase mixture is added again, and the addition amount is 17.5% of the volume of the added oil phase mixture. The addition process is slightly stirred for 20 min, and then filtered and washed with pure water until it is clear and the pH is neutral to obtain a leaching resin.
[0064] Provided is an application of the leaching resin prepared in Example 1 in purifying ammonium rhenate, specifically comprising: The ammonium rhenate solution with a concentration of 28 g / L in the copper smelting system was injected into the chromatography column containing the leaching resin prepared in Example 1 above, and passed through at a flow rate of 2 Bv to obtain a high-purity ammonium rhenate solution, which was heated for crystallization and washed to obtain an ammonium rhenate product. The results of the analysis and determination are shown in Table 1 below: Table 1 Analysis and determination results (I)
[0065] According to Table 1, the leaching resin prepared in Example 1 of the present invention enables the purity of the ammonium rhenate products of the two samples to reach ≥99.99% after purification, indicating that the leaching resin prepared in the present invention has a very significant purification effect on ammonium rhenate and can improve the purity of ammonium rhenate to an extremely high level.
[0066] Example 2 A leaching resin is prepared, comprising: (1) Mix 50 ml of ultrapure water, 45 ml of aqueous ammonia and 5 g of sodium hydroxide to obtain an aqueous phase mixture; (2) Mix 75 ml of 260# sulfonated kerosene, 20 ml of diisooctyl phosphate and 5 ml of sec-octanol to obtain an oil phase mixture; (3) Add 5 g of guar gum and 40 g of gelatin into pure water at a temperature of 80 °C, stir and dissolve, then add 10 g of styrene, 5 g of divinylbenzene, 5 g of methacrylic acid, 15 g of sodium dodecylbenzene sulfonate, 5 g of sodium carboxymethyl cellulose, 5 g of calcium sulfate and 10 g of benzoyl peroxide to the obtained colloidal solution in sequence, heat to 95 °C, stir and mix thoroughly, keep warm for 2 h, then cool, filter and wash to obtain the desired solid phase resin particles; (4) Add the obtained solid phase resin particles to an equal volume of pure water, control the pure water temperature to 60 °C, slowly add the above-mentioned oil phase mixture to the obtained system, stir lightly during the addition process, the volume ratio of the solid phase particles to the oil phase mixture added thereto is 1:0.6, stir for 30 min, keep warm for 1 h, then cool to room temperature, add the above-prepared water phase mixture, the addition amount is 15% of the volume of the added oil phase mixture, stir lightly during the addition process, the stirring time is 20 min, then filter, wash with pure water until clear and pH is neutral, and obtain leaching resin.
[0067] Provided is an application of the leaching resin prepared in Example 2 in purifying ammonium rhenate, specifically comprising: taking an ammonium rhenate solution with a concentration of 5 g / L in a molybdenum smelting system, injecting it into a chromatography column filled with the leaching resin, passing it through at a flow rate of 5 Bv to obtain a high-purity ammonium rhenate solution, heating, crystallizing, and washing to obtain an ammonium rhenate product, analyzing and measuring it, and the results are shown in the following table: Table 2 Analysis and determination results (II)
[0068] According to Table 2, the difference between Example 1 and Example 2 is that the component content, preparation parameters, etc. are slightly different. The leaching resin prepared in Example 2 still has a very significant purification effect on the two samples, and ammonium rhenate with a purity greater than 99.99% can be obtained, indicating that the present invention limits the amount of each component, so that the prepared leaching resin has a stronger adsorption performance for ammonium rhenate than the traditional leaching resin, and can be better suitable for purifying ammonium rhenate.
[0069] In summary, the leaching resin obtained by the preparation method provided by the present invention can remove impurity components in ammonium rhenate with high selectivity and efficiency to obtain a high-purity ammonium rhenate product, and the extractant can be uniformly immobilized on the resin with high strength, has stable properties and a large loading capacity, and has an increased number of cycle service life. The leaching resin has the advantages of both the extractant and the resin.
[0070] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0071] Although the preferred embodiments of the present application have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the embodiments of the present application.
[0072] Finally, it should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or terminal device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or terminal device. In the absence of further restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the process, method, article or terminal device including the elements.
[0073] The above is a detailed introduction to the preparation method of a leaching resin provided by the present application and its application in the purification of ammonium rhenate. Specific examples are used in this article to illustrate the principle and implementation method of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea; at the same time, for those skilled in the art, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A method for preparing a leaching resin, characterized in that: The method comprises: The resin particles are added to an equal volume of pure water at a temperature of 55°C to 65°C, the oil phase mixture is added to the obtained system, stirred, cooled, and then the water phase mixture is added, stirred, filtered, and washed to obtain the leaching resin; Wherein, the volume ratio of the resin particles to the oil phase mixed liquid is 1:(0.4-0.7); the volume ratio of the oil phase mixed liquid to the water phase mixed liquid is 1:(0.6-0.75); The oil phase mixed liquid is composed of 65% to 80% by weight of a diluent, 20% to 30% of a lipid compound and 5% to 10% of octanol; The aqueous phase mixed liquid is composed of 35% to 50% pure water, 25% to 45% ammonia water and 5% to 10% sodium hydroxide in percentage by mass.
2. The method for preparing the leaching resin according to claim 1, characterized in that: The volume ratio of the resin particles to the oil phase mixed liquid is 1:(0.5-0.6).
3. The method for preparing the leaching resin according to claim 1, characterized in that: The lipid compound is diisooctyl phosphate and / or 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester.
4. The method for preparing the leaching resin according to claim 1, characterized in that: The diluent is 260# sulfonated kerosene, n-dodecane or xylene.
5. The method for preparing the leaching resin according to any one of claims 1 to 4, characterized in that: The method for preparing the resin particles comprises: Gul gum and gelatin are added to pure water at a temperature of 70°C to 80°C, hydrocarbon compounds, sodium dodecylbenzene sulfonate, an initiator, sodium carboxymethyl cellulose and calcium sulfate are added to the obtained colloidal solution, mixed at 90°C to 95°C, kept warm for 2 h to 4 h, cooled, filtered and washed to obtain the resin particles; Wherein, the hydrocarbon compound is at least one of styrene, methacrylic acid and divinylbenzene; The initiator is a peroxide initiator or an azo initiator.
6. The method for preparing the leaching resin according to claim 5, characterized in that: In the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 5% to 10%, 25% to 40%, 15% to 30%, 10% to 15%, 5% to 10%, 2% to 6% and 1% to 5%, respectively.
7. The method for preparing the leaching resin according to claim 6, characterized in that: In the resin particles, the mass percentages of the guar gum, the gelatin, the hydrocarbon compound, the sodium dodecylbenzene sulfonate, the initiator, the sodium carboxymethyl cellulose and the calcium sulfate are 7% to 9%, 30% to 35%, 20% to 25%, 11% to 13%, 6% to 8%, 2% to 6% and 1% to 5%, respectively.
8. The method for preparing the leaching resin according to claim 5, characterized in that: The hydrocarbon compounds are styrene, methacrylic acid and divinylbenzene; The mass percentages of the styrene, the methacrylic acid and the divinylbenzene are (45-55)%: (20-25)%: (20-25)%.
9. The method for preparing the leaching resin according to claim 5, characterized in that: The peroxide initiator is benzoyl peroxide, dicumyl peroxide or di-tert-butyl peroxide; The azo initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
10. Use of a leaching resin in purifying ammonium rhenate, characterized in that: The leaching resin is prepared by the preparation method according to any one of claims 1 to 9, and the leaching resin is used to purify ammonium rhenate; The purification method comprises: An ammonium rhenate solution with a concentration of no more than 35 g / L is injected into the chromatography column containing the leaching resin at a flow rate of 2 Bv~7 Bv, and ammonium rhenate with a purity greater than 99.99% is obtained after passing through.
Citation Information
Patent Citations
Trialkylamine extraction resin for molybdenum-rhenium separation and its preparation method
CN102268547A
Method for recycling molybdenum and rhenium from molybdenum concentrate pressure leachate
CN103924081A
Method for recovering rhenium from molybdenum smelting waste acid by using secondary amine impregnated resin
CN113564389A
Leverage resin, preparation method thereof and preparation method of high-purity cobalt
CN117384317A